Tide and Tidal Currents in the Cape Verde Archipelago - Gomes,Nilton (2015)
The hydrography and oceanography in deep ocean areas are expensive if based only upon fieldwork and, as a result, countries with smaller financial resources have few data from in situ measurements. This work aims to contribute to demonstrate that based on little local information it is possible to increase our knowledge through the use of numerical models. This paper describes a study of the tidal propagation in the Cape Verde Islands region and the currents induced by the tide assesses the importance of the wind for the circulation using the numerical model MOHID in a two-dimensional mode. The bathymetric data were extracted from the database of NASA SRTM 30 (Shuttle Radar Topography Mission) and the coast line was extracted from the database of NGDC (National Geophysical Data Center). The tide along the oceanic boundary of the model was imposed using the results from the FES2004 model and the wind was imposed using the GFS (Global Forecasting System) meteorological model results. The modeling system is based on a regional scale model with a spatial step of 6 km (level 1) in which two models with a spatial step 3 km (level 2) were fitted to detail the results of the flow in shallower areas of greater morphological complexity where a 2D model and reproduce the effect of wind forcing. Comparison between computed and measured levels in a station located in Palmeira harbor, Sal Island - the only available measuring station - for the year 2000, shows that the model is able to represent the tide in this location. The model results also show that the currents in the shallower areas along and between islands are very sensitive to the atmospheric forcing, suggesting that this sensitivity may extend to zones of greater depth in the presence of vertical stratification. The residual circulation is the main product of this study with interest for coastal management. It is a completely new result, about which there was no information either from field work or from other models.